Pengaruh Sales Promotion dan Shopping Lifestyle terhadap Impulse Buying pada Pelanggan Golden Swalayan di Kota Kediri - Siti Patimah; Musthofa Hadi (Jurnal Riset dan Inovasi Manajemen, 2024)
In the era of modern free trade, competition in the retail industry has become increasingly fierce, prompting Golden Swalayan, a shopping center in Kediri City, to continuously enhance its sales to remain competitive. This study aims to analyze the influence of sales promotion and shopping lifestyle on the Impulse Buying behavior of Golden Swalayan customers. Using a quantitative method, data was collected through questionnaires distributed directly to 100 customers using purposive sampling techniques. Data analysis was conducted using multiple regression and hypothesis testing. The results of the study show that, both partially and simultaneously, sales promotion and shopping lifestyle have a significant influence on Impulse Buying. Based on these findings, Golden Swalayan is advised to regularly increase cashback promotions and expand its product collections to align with customers' hobbies and needs, thereby boosting Impulse Buying.